PygmyBrowse: A small screen tree browser - Zvi Band; Ryen W. White (CHI'06: Extended abstracts of the SIGCHI conference on Human Factors in Computing Systems, 2006)
We present PygmyBrowse, a browser that allows users to navigate a tree data structure in a limited amount of display space. A pilot evaluation of PygmyBrowse was conducted, and results suggest that it reduces task completion times and increases user satisfaction over two alternative node-link tree browsers.